The effect of the A.D.D.I.E. model on the achievement of first-year middle school students in social studies and the development of their visual intelligence - Ass.Lect Qaed Rahim Maan Al-Shammari (Journal of College of Education, 2026)
The study aimed to study the impact of the ADDIE model on enhancing the achievement of first-grade middle school students in social studies and developing their visual intelligence. To achieve the study objectives, a descriptive-analytical approach was adopted, and a questionnaire was used as the study tool. The research population consisted of all first-grade middle school social studies teachers in public schools in the city of Wasit. A random sample representing (50) male and female teachers was selected from the total population. The results showed that the ADDIE model had a positive and statistically significant impact on both academic achievement and the development of visual intelligence among first-grade middle school students in social studies. Based on this, the study concluded with several recommendations, including: the need to train social studies teachers, and teachers in general, on how to apply the stages of the ADDIE model in preparing and planning their lessons; and the integration of educational activities and materials that enhance visual intelligence, such as maps and visual simulations, into the curriculum.